Evaluation of trees and shrubs for oil sands reclamation field trial results ... - Consultants, Russell Ecological (University of Alberta Library, 1987)
The Alberta Oil Sands Environmental Research Program (AOSERP) Subproject VE 7.1 was initiated to select suitable tree and shrub species for use in revegetating spoils and tailings resulting from oil sands mining operations in northeastern Alberta. As part of this program three field trials were established near the Mildred Lake field camp, approximately 38 km north of Fort McMurray, in 1980 and 1981. The purpose was to test one or more provenances (seed sources) of promising native and exotic woody species. The trial site was prepared to simulate an oil sands reclamation situation. Overburden and peat were hauled to the site from Syncrude Canada Ltd.’s mining lease and incorporated in native sand. The resulting reconstructed soil was alkaline (pH 7.5), non-saline, and low in available N, P, and K. No fertilizers were added. A fine-mesh fence was erected around the trial site to exclude small mammals. All species were outplanted as one- or two-year-old container stock. All seed used to rear the native species ...